Vacuum Consolidation in Peat - O'Kelly, Brendan (My University, 2012)
Vacuum consolidation is a ground improvement technique to induce settlement and increase shear strength by applying a vacuum pressure to the ground. A pilot vacuum consolidation field trial, covering a 10x10m area, has been completed at Ballydermot bog, County Offaly, in order to study the behaviour of a peat deposit under vacuum consolidation. The test area was heavily instrumented and the test was carried out over an eleven months period. The project was part of a research project into the improvement and upgrade of rampart roads, which was sponsored under the NRA Research Fellowship Programme. This presentation describes the principles of vacuum consolidation practice and the extent of its current application worldwide. Details will be given of the construction and instrumentation of the field trial at the Ballydermot site and of the geotechnical properties of the peat and underling glacial till. Experimental results of the field trial will be presented along with the practical aspects concerning the application of this technique for peat deposits. The field response under vacuum consolidation will also be compared with that estimated by finite element modelling using laboratory-derived soil parameters.
Invited Presentation (Continuing Professional Development Lecture), Geotechnical Society of Ireland, Engineers Ireland
PUBLISHED
Webcast and Powerpoint presentation are both available for download.
Dublin, Ireland
Keywords: Consolidation; Ground improvement; Peat; Preloading; Settlement; Soft soil; Vacuum